Bait [videorecording (DVD)] - Jenkin, Mark; Rowe, Edward (Actor); King, Giles; Endean, Chloe (Neon, 2023)
After his brother makes the unilateral decision to change their family's livelihood and home to attract tourists, a cove fisherman struggles to restore his family to their traditional place when a tragedy changes his world.